AN UNUSUAL RECORD OF AN ANDEAN PASSERINE, THE BLACK-BACKED GROSBEAK, IN SOUTHEASTERN BRAZIL - Antonelli, Victor R. [UNESP]; Cavarzere, Vagner [UNESP] (Aves Argentinas / Asociacion Ornitologica del Plata, 2024)
The Black-backed Grosbeak (Pheucticus aureoventris) is common on eastern Andean slopes from Venezuela to Argentina. In Brazil, it is a regular non-breeding visitor in the west, using large rivers of the Paraná basin as movement routes, especially during the austral winter, when most records in the country are concentrated. We present a novel observation of the species from the mid-central region of São Paulo state, southeastern Brazil, approximately 400 km east of its known range. Considering the uncertain migratory routes of the Black-backed Grosbeak to Brazil, we gathered additional rare sightings from the country that, when combined with our own, suggest the species’ propensity for extensive dispersal.
El registro poco común de un ave paseriforme andina, el Picogrueso Dorsinegro, en el sureste de Brasil
Keywords: Cerrado; geographical distribution; lBlack-backed Grosbeak; migrant birds; São Paulo